2014
DOI: 10.4292/wjgpt.v5.i3.156
|View full text |Cite
|
Sign up to set email alerts
|

Renal dysfunction in patients with cirrhosis: Where do we stand?

Abstract: Patients with cirrhosis and renal failure are high-risk patients who can hardly be grouped to form precise instructions for diagnosis and treatment. When it comes to evaluate renal function in patients with cirrhosis, determination of acute kidney injury (AKI), chronic kidney disease (CKD) or AKI on CKD should be made. First it should be excluded the prerenal causes of AKI. All cirrhotic patients should undergo renal ultrasound for measurement of renal resistive index in every stage of liver dysfunction and ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 119 publications
(167 reference statements)
0
16
0
1
Order By: Relevance
“…Intercurrent illness such as peritonitis or gastrointestinal haemorrhage should also be excluded as this may be contributing to or precipitating renal dysfunction. 6,21 Management Treatment should target the underlying aetiology and will depend on the severity. It may include supportive and antimicrobial therapies, specific treatments for HRS and the Urine outflow obstruction due to, for example, prostatic hypertrophy, a pelvic mass or bleeding in the urinary tract Chronic kidney disease and liver disease Hepatorenal syndrome type 2 Polycystic kidney and liver disease Glomerulonephritis (e.g.…”
Section: Definition Of Hepatorenal Syndromementioning
confidence: 99%
“…Intercurrent illness such as peritonitis or gastrointestinal haemorrhage should also be excluded as this may be contributing to or precipitating renal dysfunction. 6,21 Management Treatment should target the underlying aetiology and will depend on the severity. It may include supportive and antimicrobial therapies, specific treatments for HRS and the Urine outflow obstruction due to, for example, prostatic hypertrophy, a pelvic mass or bleeding in the urinary tract Chronic kidney disease and liver disease Hepatorenal syndrome type 2 Polycystic kidney and liver disease Glomerulonephritis (e.g.…”
Section: Definition Of Hepatorenal Syndromementioning
confidence: 99%
“…Prerenal azotemide tedavi; izotonik intravenöz sıvı resüsitas-yonu, diüretiklerin kesilmesi ile renal kan akımı ve övoleminin sağlanması, gastrointestinal kanaması olanlarda eritrosit süspan-siyonu ve plazma genişletici verilerek hemodinamik stabilitenin korunması (replasmanda hedef hemoglobin 7 gr/dL), ciddi asiti olan hastalarda geniş volümlü parasentezin 8 gr/L albümin infüzyonu eşliğinde yapılması ve bakteriyel enfeksiyon varsa agresif tedavi edilmesi (3. kuşak sefalosporinler) ilkelerini kapsamalıdır. Yine sirozda ve asiti olan hastalarda nefrotoksik ajanlardan, kontrast maddelerden ve hipotansiyona yol açabilecek ajanlardan kaçınılmalıdır (21,22). Tablo III'te dikkatle kullanıl-ması ve kaçınılması gereken ilaçlara kısaca değinilmiştir (18).…”
Section: Tedavi Yaklaşımlarıunclassified
“…However nevertheless, serum creatinine which is used to analyze MELD score, should be interpreted with caution, since there is no universal standardized creatinine assay; there are interlaboratory variations, interactions with bilirubin and great influence by numerous nonrenal factors such as body weight, race, age, and gender. 14 Our study showed that esophageal varices (66.7%), use of diuretics (47.6%) and presence of diarrhoea and vomiting (23.8% each) were major cause of acute kidney injury alone or in combination. Whereas along with this the risk factors for development of hepatorenal syndrome was studied which showed that presence of subacute bacterial peritonitis (88 % vs 18.3%, p<0.0001), GI bleed (50% vs 23.2%, p=0.022) were major factors that were significantly associated with development of HRS.…”
mentioning
confidence: 99%
“…Martín-Llahí et al (14) discussed this drawback by the absence of specific markers that may help in the identification of the cause of renal failure in cirrhosis. We also recommend the need to exert an effort to build-up a new battery of laboratory markers of renal failure that may be useful for the differential diagnosis.…”
mentioning
confidence: 99%